Adenosine A2A receptor modulates microglia-mediated synaptic pruning of the retinogeniculate pathway during postnatal development. (1st December 2021) - Miao, Yaxin; Chen, Xuhao; You, Feng; Jia, Manli; Li, Ting; Tang, Ping; Shi, Ruyi; Hu, Shisi; Zhang, Liping; Chen, Jiang-Fan; Gao, Ying
Abstract: Synapse pruning is essential not only for the developmental establishment of synaptic connections in the brain but also for the pathogenesis of neurodevelopmental and neurodegenerative disorders. However, there are no effective pharmacological means to regulate synaptic pruning during early development. Using the eye-specific segregation of the dorsal lateral geniculate nucleus (dLGN) as a model of synaptic pruning coupled with adenosine A2A receptor (A2A R) antagonism and knockout, we demonstrated while genetic deletion of the A2A R throughout the development attenuated eye-specific segregation with the attenuated microglial phagocytosis at postnatal day 5 (P5), selective treatment with the A2A R antagonist KW6002 at P2–P4 facilitated synaptic pruning of visual pathway with microglial activation, increased lysosomal activity in microglia and increased microglial engulfment of retinal ganglion cell (RGC) inputs in the dLGN at P5 (but not P10). Furthermore, KW6002-mediated facilitation of synaptic pruning was activity-dependent since tetrodotoxin (TTX) treatment abolished the KW6002 facilitation. Moreover, the A2A R antagonist also modulated postsynaptic proteins and synaptic density at early postnatal stages as revealed by the reduced immunoreactivity of postsynaptic proteins (Homer1 and metabotropic glutamate receptor 5) and colocalization of presynaptic VGlut2 and postsynaptic Homer1 puncta in the dLGN. These findings suggest that A2A R can control pruning by multiple actions involving the retinal wave, microglia engulfment, and postsynaptic stability. Thus, A2A R antagonists may represent a novel pharmacological strategy to modulate microglia-mediated synaptic pruning and treatment of neurodevelopmental disorders associated with dysfunctional pruning. Highlights: A2A R KO tended to delay eye-specific segregation and decreased microglia phagocytosis. The A2A R antagonist KW6002 enhanced eye-specific segregation at P5 but not P10. KW6002 facilitated eye-specific segregation at P5 in an activity-dependent manner. KW6002 activated the microglia and enhanced the engulfment of RGC inputs in the dLGN. KW6002 decreased both the density of postsynaptic proteins Homer1/mGluR5 and synapse.